2005
DOI: 10.1029/2004jb003433
|View full text |Cite
|
Sign up to set email alerts
|

Detailed structure and sharpness of upper mantle discontinuities in the Tonga subduction zone from regional broadband arrays

Abstract: [1] Recordings of deep Tonga earthquakes from two arrays of 12 broadband seismographs each in the Fiji and Tonga islands are stacked and searched for reflections and conversions from upper mantle discontinuities in the Tonga subduction zone. The arrays operated as part of the Seismic Arrays in Fiji and Tonga (SAFT) experiment from July 2001 to August 2002. In comparison with the commonly used teleseismic approaches, the short path lengths for the local data provide smaller Fresnel zones and high-frequency cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 70 publications
4
28
0
Order By: Relevance
“…Moreover, the discontinuity almost disappears for the high 40% iron content. These transitions contrast with those on Earth, for which both the reduced iron content and the higher pressure gradient result in sharp discontinuities, with a typical width of < 10 km (e.g., Tibi and Wiens, 2005). Reflections from mantle discontinuities on Mars might be less impulsive than reflections on Earth, and as a result, they might only be observable only at LPs, when the seismic wavelength is much greater than the width of the discontinuity, or below frequencies of 0.05-0.1 Hz.…”
Section: Giant Planets Seismologymentioning
confidence: 90%
“…Moreover, the discontinuity almost disappears for the high 40% iron content. These transitions contrast with those on Earth, for which both the reduced iron content and the higher pressure gradient result in sharp discontinuities, with a typical width of < 10 km (e.g., Tibi and Wiens, 2005). Reflections from mantle discontinuities on Mars might be less impulsive than reflections on Earth, and as a result, they might only be observable only at LPs, when the seismic wavelength is much greater than the width of the discontinuity, or below frequencies of 0.05-0.1 Hz.…”
Section: Giant Planets Seismologymentioning
confidence: 90%
“…Xu et al (1998) and Xu et al (2003) found globally a sharp 660 (2 km or less) and a less sharp 410 from P 0 P 0 precursors. Tibi and Wiens (2005) concluded from short-period observations of local earthquakes a sharpness of 0-2 km for the 660 and 2-10 km for the 410 in the Tonga subduction zone. Castle and Creager (2000) identified that the 660 is locally < 10 km wide at the Izu-Bonin subduction zone using source side S-to-P conversions recorded in the western United States.…”
Section: Sharpness Of 410 and 660mentioning
confidence: 99%
“…Gilbert et al (2001) confirmed such observations with ocean-bottom seismic data. Tibi and Wiens (2005) studied the 410 and 660 with local high-frequency seismic phases recorded by an array of broadband island stations. Tibi and Wiens (2005) studied the 410 and 660 with local high-frequency seismic phases recorded by an array of broadband island stations.…”
Section: Chinamentioning
confidence: 99%
“…Castle and Creager (2000) found that the 660 is locally less than 10 km wide at the Izu-Bonin subduction zone using source side S-to-P conversions recorded in the western United States. Tibi and Wiens (2005) concluded from shortperiod observations of local earthquakes a sharpness of 0-2 km for the 660 and 2-10 km for the 410 in the Tonga subduction zone. Estabrook and Kind (1996) concluded from the missing precursors of PP from the 660 that the velocity and density jump here is globally significantly smaller than predicted by the IASP91 model.…”
Section: Sharpness Of 410 and 660mentioning
confidence: 99%
“…Gilbert et al (2001): Ocean-bottom receiver functions; 410 uplifted by 30 km and 660 depressed by 20-30 km. Tibi and Wiens (2005): Reflections and conversions at the 410 and 660 of local high-frequency seismic phases recorded by an array of broadband island stations; practically, no change in the 410 depth; 660 depressed to 714 km (see Figure 9). Tibi and Wiens (2005): Reflections and conversions at the 410 and 660 of local high-frequency seismic phases recorded by an array of broadband island stations; practically, no change in the 410 depth; 660 depressed to 714 km (see Figure 9).…”
Section: Global Transition Zone Structurementioning
confidence: 99%